2017
DOI: 10.1111/jspn.12201
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a virtual reality intervention to minimize pediatric stress and pain intensity during venipuncture

Abstract: Purpose: Virtual reality (VR) technology is an effective tool in treatment of acute pain. Numerous studies show the effectiveness of this method both in a clinical context and in the laboratory. However, research results on the effectiveness of VR in pediatric venipuncture pain is not conclusivenot all studies report the analgesic effect of VR. In addition to testing effectiveness of VR, we also assess the usability of a novel hands-free interface. Practice Implications: VR can be as an effective tool to minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
136
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(149 citation statements)
references
References 35 publications
8
136
0
5
Order By: Relevance
“…Additional questions regarding patient satisfaction found that all patients in both treatment groups were satisfied with their experience. All but one patient using IVR distraction would Pre-procedure Emotion-B score 7 (5, 8) 7 (6,9) Presented are N (%) or median (interquartile range).…”
Section: Midazolam and Fentanyl Administration During The Procedures mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional questions regarding patient satisfaction found that all patients in both treatment groups were satisfied with their experience. All but one patient using IVR distraction would Pre-procedure Emotion-B score 7 (5, 8) 7 (6,9) Presented are N (%) or median (interquartile range).…”
Section: Midazolam and Fentanyl Administration During The Procedures mentioning
confidence: 99%
“…There have been several other studies that demonstrate a sedation or analgesic sparing effect of IVR [7][8][9][10][11]. Further efforts have also been made to commercialize IVR, with little high-quality evidence of effectiveness [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main focus of this study is VR distraction analgesia. VR has shown promising results in reducing pain, anxiety and stress during painful procedures, including during wound dressing changes in burn wound patients and chronic wound patients, dental procedures, and venepuncture [12][13][14][15][16] . Most studies to date have reported an analgesic effect of VR when compared with standard care (no distraction) during painful procedures.…”
mentioning
confidence: 99%
“…What is more, promising results have been found for hypnosis interventions that can reduce children's anxiety when undergoing needle procedures (Nunns et al, ). A further type of intervention which seems to be an effective way of minimizing the stress and pain that arise from needle procedures is virtual‐reality distraction (Piskorz & Czub, ). In light of this, healthcare professionals should actively listen to parents’ and children's anxieties and offer them advice on factors that might help alleviate the fear of needles and the unpleasantness of the actual procedures.…”
Section: Discussionmentioning
confidence: 99%